Characterisation of worn WC tool using STEM‐EDS aided by principal component analysis. (4th May 2021) - Lazar, Isac; Lindvall, Rebecka; Lenrick, Filip; Bushlya, Volodymyr; Ek, Martin
Abstract: Interdiffusion and chemical reactions contribute to tool wear in metal machining. Increased understanding of these processes, through characterisation of worn tools, can facilitate design of more resilient materials through chemical and diffusional passivation. However, the unknown reaction conditions, the large number of elements, and the formation of interspersed phases makes for a complex analysis. Here, we demonstrate the use of scanning transmission electron microscopy and energy dispersive X‐ray spectroscopy for characterising the interaction layer between a titanium alloy and a cemented carbide tool. Principal component analysis is used to find chemical correlations and help separate signals from embedded phases. Crucially, we evaluate the required X‐ray count statistics from simulated spectrum images and theory prior to the experiment. We find no indications of intermediate phases between the original WC and the metallic W interaction layer. Furthermore, we find enrichment of minor constituents in the titanium alloy closest to the tool which alter the solubility of out‐diffusing species, suggesting strong interrelations between the diffusion processes.